Developing E-Learning-Based English Material for Teaching the Tenth Grade Students of Light Vehicle Department at SMK N Bali Mandara - Ni Made Dwi Putri Widiantarai (Universitas Pendidikan Ganesha, 2017)
This study aimed at: (1) identifying e-learning based English materials which were needed by the tenth grade students of Light Vehicle Department at SMK N Bali Mandara; (2) identifying the design of the e-learning based English materials for the tenth grade students of Light Vehicle Department at SMK N Bali Mandara; (3) measuring the quality of the e-learning based English materials for the tenth grade students of Light Vehicle Department at SMK N Bali Mandara. This study applied Research and Development designed by Lee and Owens (2004). The data of the study were collected through document analysis, questionnaire, and expert judge. The results of the data from the document analysis and questionnaire were analyzed descriptively; the data from expert judge was analyzed quantitatively by using a formula proposed by Candiasa (2010). The result of the study showed that the tenth grade students of Light vehicle Department at SMK N Bali Mandara were still taught using general English and the students needed English materials which were developed in accordance with their expertise program. Thus, this study developed four topics based on the students’ expertise, namely: 1) Describing Hand Tools; 2) Signs at the Workplace; 3) Stating Capabilities in Repairing Car; and 4) Inviting Customer. Each topic was designed using Moodle version 3.3.x and focused on improving the students’ four language skills. Based on the result of expert judgment, the mean score from both judges was 92 and was categorized as good materials.